PENGARUH RISIKO, INTERNAL AUDITING, GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN TINGKAT SUKU BUNGA TERHADAP KINERJA PERUSAHAAN DAN REAKSI PASAR (STUDI PADA BUMN YANG TELAH MENCATATKAN SAHAMNYA DI BURSA EFEK INDONESIA) - A. Yaniarsyah Hasan (Indonesian Journal of Economics and Business, 2011)
This study consists of 2 (two) research, namely: (1) Research that aims to see the Influence of risk, Internal Auditing, Good Corporate Governance (GCG), Firm Size (Size) and Interest Rates (SBI) on the performance of companies with profit margins and stock return proxy in relation to preparing an appropriate strategy to achieve performance the company planned, (2) This study aimed to see the market reaction in the form of share price at the time of the announcement of the annual report together with the Revenue Budget and Work Plan (RKAP).  Research on variables that affect firm performance variable aims to find those variables that affect the company's performance so the company can prepare appropriate strategies to achieve corporate performance is planned. Research about the market reaction upon announcement of the annual report aimed to see how the market perception was reflected in the stock price at the time of the announcement of the annual report. The announcement of the annual report is an event awaited by the markets as describe inside in the agenda: accountability for managing the company's management, the uses of profit sharing included dividend policy and RKAP Both studies use survey methods and analysis unit of 15 (fifteen) BUMN (which are listed on the Indonesia Stock Exchange), which became the unit as well as analysis of secondary data obtained from Indonesia Stock Exchange (IDX), Bank Indonesia, Indonesian Institute for Corporate Governance and others sources of data. This study uses Econometric Model with statistical techniques multiple regression to see the influence of risk, Internal Auditing, GCG, Size and interest rates variable on the performance of the company, to research on market reactions using Event Study.  The Conclusion of this research and discussion after the test is as follows: Firm performance is influenced by risk and interest rates. GCG effect on stock returns and the GCG implementation has yet reached the trustworthy level.Internal Auditing affected the profit margin and Implementation of Internal Auditing have yet  to  include the entire program to be implemented. Firm Size does not influence the performance of the company Market reaction occurred in the form of rising stock prices during the announcement of the annual report and RKAP.